KEMAMPUAN LITERASI NUMERASI DITINJAU DARI RESILIENSI MATEMATIS PESERTA DIDIK KELAS VII DI SMP NEGERI 1 SUNGGAL T.A 2024/2025 - Sitorus, Ruth Serenata; Panjaitan, Simon; K Sitepu, Christina Purnamasari (Jurnal Curere, 2024)
This study aims to determine the numeracy literacy ability of students as reviewed from the mathematical resilience of grade VII students at SMP Negeri 1 Sunggal T.A 2024/2025. This study uses indicators of Numeracy Literacy and Mathematical Resilience, where the measurement method is through high, medium and low assessments. The type of research used in this study is qualitative descriptive. To obtain the data, data collection techniques were used which included numeracy literacy tests and questionnaires. The data analysis technique uses the theory of Miles and Huberman, namely reducing data, presenting data and inferring data. The results of this study show that the numeracy literacy ability is not completely good, where the percentage of students with low ability is more than the percentage of students with medium and high ability. For Mathematical Resilience, students are included in good because the percentage of high-ability students is more than the percentage of medium- and low-ability students.